Demystifying cultural intermediaries: Who are they, what do they do and where can they be found in England? - Lisa De Propris; Samuel Mwaura (University of Birmingham, Birmingham Business School, 2013)
The object of this paper is to reconceptualise cultural intermediaries and cultural intermediation in a way that may not only allow a coherent understanding of the various functions associated with these actors, but may also enable systematic empirical analyses of their effects on other cultural, social and economic phenomena. This paper employs a value chain approach to develop a typology of cultural intermediation that may enable a more systematic analysis of cultural intermediaries and cultural intermediation. It presents maps of cultural intermediation in England as well as the three major cities: London, Birmingham and Manchester.
Keywords: 330; Cultural industries; cultural intermediation